Keanekaragaman dan Kelimpahan Belalang dan Kerabatnya (Orthoptera) pada Dua Ekosistem Pegunungan di Taman Nasional Gunung Halimun-Salak - NETY VIRGO ERAWATI; SIH KAHONO (Perhimpunan Entomologi Indonesia, 2010)
A study on diversity and abundance of grasshopper and its relatives (Orthoptera) was conducted at two mountainous rainforest ecosystems (Mounts Kendeng and Botol) of Gunung Halimun-Salak National Park. A hundred meters of a line transect was used to sample and set up several insect traps (yellow pan, malaise, pit fall, bait pit fall, sweep net, and light traps), and insect sweepings as well. The light traps were set up at about fifty meters distance from the end of the sampling sites. A total individual collected by traps was combined on every comparable sampling site. Total individuals of the Orthoptera captured were 414; consisted of 25 species of 9 families. Both species diversity and number of families were higher at Mount Kendeng rather than Mount Botol. Number of species of each family usually similar except on family of Grillidae was much higher at Mount Kendeng. Species belong to Phasmidae was not recorded at Mount Kendeng, while species belong to both families of Gryllotalpidae and Tettigonidae were not captured at Mount Botol as well. Overal there was a difference in the species richness at each between. Shannon Diversity Index (H’) and evenness (E) were higher at Mount Kendeng (2.44 and 0.81) rather than Mount Botol (1.80 and 0.66). Similarity Index of Jaccard (Cj) and Sorenson (Cn) of both localities were similar (0.40 and 0.32). Herbivores were most dominant at both localities (Phasmidae, Tetrigidae, Acrididae, Gryllidae, dan Gryllotalpidae), followed by omnivores (Blattidae), scavenger (Gryllacrididae), and predator (Mantidae).